GENERAL CHARACTERISTICS OF THE STATUS OF SELF-EMPLOYED PERSONS - Багірова, Ганна Ігорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to explore the legal regulation of the self-employed persons in Ukraine by the current domestic legislation. Methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: insufficient theoretical elaboration of the problems of legal personality of self-employed persons, which is explained by the haphazard development of law enforcement activity in the research sphere. Discussion: found that there is no single clear understanding among scholars of the relation of the category «self-employed person» with the category «entrepreneurship», which in turn is a significant flaw in the field of legal regulation. The question of the general characteristics of self-employed persons is quite relevant, since there is a lack of theoretical elaboration of the problems regarding the status of self-employed persons, which is explained by the systematic development of law enforcement activities in the research field. In addition, it is necessary to determine the relationship between the rights and obligations of self-employed persons and other taxpayer individuals. The purpose of the article is to reveal the general characteristics of self-employed persons in Ukraine, taking into account theoretical and practical aspects and defining scientific views on this category. Therefore, the main reasons for the problems in the legal regulation of self-employed persons are the obsolescence of legislative norms regarding employment and employment. You can also conclude that there is no clear legislative definition of the concept of «self-employed persons», its identity with the concept of «self-employed persons», the absence of an exhaustive legislative list of entities belonging to this category. In this regard, the issue of defining a unified approach to the legislative consolidation of the concept of self-employed persons, a clear definition of the circle of these persons, the regulation of the relevant rules of law is quite urgent.